2015
DOI: 10.1007/s00354-015-0102-0
|View full text |Cite
|
Sign up to set email alerts
|

Projective Simulation for Classical Learning Agents: A Comprehensive Investigation

Abstract: We study the model of projective simulation (PS), a novel approach to artificial intelligence based on stochastic processing of episodic memory which was recently introduced [1]. Here we provide a detailed analysis of the model and examine its performance, including its achievable efficiency, its learning times and the way both properties scale with the problems' dimension. In addition, we situate the PS agent in different learning scenarios, and study its learning abilities. A variety of new scenarios are bei… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
118
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 46 publications
(119 citation statements)
references
References 18 publications
0
118
1
Order By: Relevance
“…As shown in previous works, [1,2] the PS performance depends on the value of its internal γ and η damping parameters. In particular, it was shown that a nonzero damping parameter γ, i.e.…”
Section: Grid Worldmentioning
confidence: 51%
See 3 more Smart Citations
“…As shown in previous works, [1,2] the PS performance depends on the value of its internal γ and η damping parameters. In particular, it was shown that a nonzero damping parameter γ, i.e.…”
Section: Grid Worldmentioning
confidence: 51%
“…Following previous studies of projective simulation (PS), in which the novel model was shown to perform well on several toy-problems, [1,2] in this paper we studied the model in more challenging scenarios. In particular, we studied the performance of the PS agent in the navigation tasks of gridworld and mountain-car, in which an agent is supposed to learn how to find a goal in minimal number of steps.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a huge number of recent papers using machine learning (ML) to train artificial neural networks to implement algorithms and protocols, for example, for classifying data. There is an excellent review article by Biamonte et al [217] which, together with a number of recent research papers on Hopfield recurrent QNNs, [218,219] quantum Boltzmann machines, [220,221] quantum circuit QNNs, [222,223] and quantum agents and artificial intelligence, [224][225][226][227][228][229] covers most of the field.…”
Section: Machine Learning In Feed-forward and Recurrent Qnnsmentioning
confidence: 99%